1986
DOI: 10.1017/s0022172400066067
|View full text |Cite
|
Sign up to set email alerts
|

Rubella epidemiology in South East England

Abstract: SUMMARYAnalyses of data collected in a large survey (sample size > 3000) of rubella antibody in South East England, finely stratified according to age, reveal age-dependent changes in the pattern of virus transmission. The rate or force of infection changes from low in the young children to high in the 5 -to 15-year-olds and back to low again in the adult age classes (there is a 50 % reduction between the 5-to 15-year-olds and the 20 + -year-olds). Raised levels of immunity are recorded in the teenage and youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…We used the radial haemolysis test to quantify rubella antibody levels in sera. This is an inexpensive test that was easy to establish in Ethiopia, and has been well evaluated in previous studies [7]. We have found that the RH assay tends to give negative results in adults who are sero-positive by ELISA and presumably have relatively low antibody levels reflecting waning immunity [12].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We used the radial haemolysis test to quantify rubella antibody levels in sera. This is an inexpensive test that was easy to establish in Ethiopia, and has been well evaluated in previous studies [7]. We have found that the RH assay tends to give negative results in adults who are sero-positive by ELISA and presumably have relatively low antibody levels reflecting waning immunity [12].…”
Section: Discussionmentioning
confidence: 95%
“…Elucidation of age differences requires large sample sizes over a wide age range and fine age stratification, ideally from representative samples of the population under study. Such studies are few [7,20,35]. A functional form for age-dependence in λ put forward by Farrington [13] and shown to fit data from widely different locations of England and Wales and Sao Paulo, Brazil, was unable to describe data from Addis Ababa adequately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sera collected in 1986 formed part of the countrywide survey of measles, mumps and rubella conducted by the Public Health Laboratory Service, summary results of which have been published [6]. 50 16 18 60-69 61 65 41 40 70-79 31 44 37 39 80+ 7 21 13 34 Total 1357 1316 1194 1157 Serological screening Mumps-specific antibodies were assayed by a radial haemolysis test, using the method previously described [6,11,12]. Screening of the 1986 samples was conducted at Preston, and the 1984 samples at Imperial College.…”
Section: Sample Collectionsmentioning
confidence: 99%